Indicadores de transporte de água no intervalo hídrico ótimo do solo - Mentges, Lenise Raquel (2017)
The need to evaluate the effect of management practices has generated interest in defining Soil Quality Indicators (SQI) that involve the management result and its effect on crop yield. In terms of water in the soil, the Last Limiting Water Range (LLWR) is a enough used SQI, but is effecacy questioned by Soil Science researchers. The criticism is due to the fact that the LLWR is often not related to grain production, or even the higher crop yields occur under conditions of higher soil compaction where the LLWR has been reduced. This study considers that the analysis of water transport indicators in the soil can help in the understanding of why plants can produce more under conditions of supposedly lower soil physical quality. Therefore, this study aimed to determine the matrix flow potential (M) and the hydraulic conductivity (K), in the LLWR of an Ultisol and an Oxisol and to evaluate how they modify the interpretation of the LLWR based only on its critical limits of water content. In both soils, the results indicated that variations of M (dM) and K increase where LLWR is reduced as a function of the increase of bulk density (Ds), indicating that it improves the capacity of the soil to conduct water, even after critical bulk density (Dsc) calculated with the LLWR. Also, the indicators correlate positively with the Ds independent of the matrix potential, improving the water transport, being this greater influence for the Ultisol. The use of the water transport indicators together with the LLWR modified the interpretation of the water supply to the plants and the correlation that this can have with crop yields, allowing to believe that soil quality indicators, defined only on the basis of water content, such as the LLWR, may not be adequate to predict the occurrence of water deficit. The beneficial effect of increasing Ds on water transport can not be analyzed individually when dealing with soil management, since increasing Ds results in undesirable soil changes, and so it is important to observe the overall effect of soil compaction. Studies with plants that evaluate the compensation of the increment of water transport on the reduction in the root growth by mechanical resistance with the increase of the compaction would be of great utility.